Penerapan Monitoring dan Controlling Suhu Ruang Server Berbasis Internet of Things (IoT) - Syafii, Olynda Mufariihana Nur; Astutik, Ika Ratna Indra; Hindarto, Hindarto (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
The server room is a space owned by every company that serves as the control center for database systems in both small and large companies. Operational activities of the server are carried out by administrators (operators) who can monitor and manage the database system on the server. The temperature in the server room is crucial for maintaining the facilities and regulating the temperature when operators are inside. From the above issues, a system can be implemented that is currently widely used by everyone, namely the use of the Internet of Things (IoT). The Internet of Things (IoT) is a concept designed to enable electronic devices to communicate autonomously and exchange data through network connections. The implementation of IoT has the potential for monitoring and control at specific locations. With the presence of IoT, it can integrate IoT, temperature sensor devices, and output applications such as Blynk and WhatsApp. Blynk facilitates the NodeMCU microcontroller and DHT22 to receive and send temperature values to users of the application. In addition to Blynk, another monitoring system uses a WhatsApp Bot that sends temperature notifications in the server room. The IoT with this concept yielded research test results, where the system facilitates users or administrators in monitoring and controlling temperature using Blynk and WhatsApp applications, benefiting from a more user-friendly interface. In conclusion, this research facilitates users or owners of server rooms to manage facilities for longer durability, and users or administrators can monitor the server room temperature without having to be inside.